Microbiota Landscape of Gut System of Guppy Fish (Poecilia reticulata) Plays an Outstanding Role in Adaptation Mechanisms - Christian Aimé Kayath; Armel Ibala Zamba; Joseph Goma-Tchimbakala; Victor Mamonékéné; Gloire Moniceth Mombo Makanga; Aimé Augustin Lebonguy; Etienne Nguimbi (International Journal of Microbiology)
Microbial consortium that is present in fish gut systems works together to achieve unknown specific roles. Here, we collected guppy fish from hydrocarbon- and trace metal-contaminated wastewater to assess the relationships between gut microbiota and host fish adaptation. Targeted genes and 16S rRNA amplicon sequencing have been used to identify gut bacteria of guppies. Mineral-conditioned medium contributes to identify bacteria with the ability to grow and/or to tolerate hydrocarbon and trace metals. Additionally, trace metals’ tolerance minimum inhibitory concentration (MIC) of microbiota was evaluated. We first isolated bacteria from the gut system, and we showed that Bacillus spp., Staphylococcus spp., Shigella spp., Salmonella spp, Pseudomonas spp., Citrobacter spp., Salmonella enterica ssp.arizonae sp., Enterobacter spp, and Acinetobacter spp. are part of guppy gut microbiota. Some representative species are able to degrade and/or tolerate gasoline and/or diesel fuel hydrocarbons. Tolerance to trace metals was observed in Gram-positive and Gram-negative bacteria. We showed that minimal inhibitory concentration (MIC) of some microbiota isolated from gut systems has been found including for mercury (Hg) between 2 and 4‰, cobalt (Co) Co (2 and 5‰), zinc (Zn) (9 and 18‰), and plomb (Pb) (22 and 27‰). Zn and Pb were the trace metals for which the rate of tolerance was significantly higher. Finally, we showed that cytochrome c oxidase is not interfering in presence of trace metals. The working consortium showed that bacteria should work together to achieve their best.